Discreet charm of the big bad wolf - McCall Smith, Alexander 1948- (New York Pantheon Books, 2023)
"The Department of Sensitive Crimes is downsizing in light of a recent downturn of sensitive crime, and staff members are wondering who among them will be transferred elsewhere. As the bickering between colleagues intensifies, Ulf tries his best to stay above the fray. But when Anna, a longtime friend and coworker, appears to blame him for an old case that went sideways, it seems she may be putting her own job prospects above their friendship. In the midst of all this, Ulf embarks on an important inquiry: a man's cabin has mysteriously disappeared and Ulf is tasked with finding out what happened. How exactly does one steal a house? And, more to the point, how does one track down a stolen house? Meanwhile, a promising veterinary treatment for deafness in dogs has been announced, and Ulf's dog, Martin, might be the perfect patient. This latest novel is another masterful, farcical installment in the series that defines the genre that Alexander McCall Smith is singlehandedly championing: Scandi blanc" --
112160
Keywords: Varg, Ulf -- (Fictitious character) -- Fiction; Police -- Sweden -- Malmo -- Fiction; Criminals -- Fiction; Criminal investigation -- Fiction; Deaf dogs -- Fiction; Sweden -- Fiction; Sweden -- Malmo; Detective and mystery fiction; Fiction; Humorous fiction; Novels; Novels